(untitled) (Ágora Journal, 2022)
This paper discusses the commemorative character of the festivities about the proclamation of Dom Pedro I as Emperor of Brazil in the small village of Itapemirim, Brazilian province of Espírito Santo in 1822. We shall not only define the elite responsible for the solemn ceremony of acclamation, but also analyze the political meanings involved in the activities. Our main research sources have been the acclamattion documents, along with the official correspondence among Itapemirim governors, provincial authorities, and Portuguese imperial officials.